Investigating the role of tumour-deposited extracellular matrix in medulloblastoma progression - Johnson, James E. C. (2023)
Introduction: The extracellular matrix (ECM) is a web of macromolecules which under normal conditions provides structural support to tissues, as well as regulating cellular differentiation, motility, migration and survival. In the past decade emerging evidence has demonstrated that tumours are able to extensively modify the composition and mechanical properties of their surrounding ECM. Tumour ECM has been shown to be pro- or anti-tumorigenic and can therefore sometimes be used to predict patient prognosis. Medulloblastoma is the most common malignant paediatric brain tumour, accounting for 10% of all cancer related deaths in children, and is the focus of this thesis. The role of tumour ECM in medulloblastoma progression is currently poorly understood. However, a recent study by our group identified ECM sub-types within the medulloblastoma molecular sub-groups, characterised by the expression of specific ECM proteins. One of these ECM sub-types was defined based on the expression of laminin in SHH and Group 4 medulloblastoma patients. High expression of laminin (LAMhigh) was shown to be associated with more favourable overall survival in SHH medulloblastoma patients, whereas low laminin expression (LAMlow) was associated with poorer survival. The opposite trend was observed in Group 4 patients. Furthermore, it was shown that SHH medulloblastoma cell lines formed a sub-group specific laminin shell-like structure when grown in long-term 3D cell culture. This study aims to delineate the underlying molecular mechanisms which potentiate this pattern of survival conveyed by laminin.